Innovative-Wear Nusantara (I-WEAR NUSA): The Implementation of Experimental Fashion Design Method through Interactive Wearable Fashion Creation - Olivia Gondoputranto (Wacana Seni Journal of Arts Discourse, 2025)
This research was based on the digital phenomenon of the Fourth Industrial Revolution with a specific focus on the fashion sector, classified as one of the largest contributors to Gross Domestic Product (GDP) but lacking in product innovation through technology application. The aim was to develop innovative clothing that integrated cultural traditions with modern advancements through the use of electro-fashion and embedded augmented reality features. The design showed the culture of Sasak Sade community as part of the indigenous tribes that had received government attention for preservation and promotion due to its local wisdom and heritage. Moreover, Innovative-Wear Nusantara (I-WEAR NUSA) was explored as an experimental fashion design method to produce clothes. The implementation of this method enabled practical experimentation in the production of innovative fashion that seamlessly combined cultural traditions with contemporary advancements through the incorporation of elements such as electro-fashion and integrated augmented reality features. The results were expected to enhance the understanding and application of technology in the fashion sector while promoting the cultural heritage of Indonesia both nationally and globally.